55.8k views
4 votes
1) f(t) = -1 + 1
g(t) = 2t + 5
Find f(3) – g(3)

User Os X Nerd
by
5.0k points

1 Answer

3 votes

Answer:

f(3)-g(3)= -13

Explanation:

The problem is asking to obtain the numerical solution for the subtraction of two given function evaluated both in t=3.

We can do that by first, evaluating the point and then performing the subtraction.

If we evaluate t=3 in f(t)= -t +1 we have f(3)=-3+1=-2

If we now evaluate t=3 in g(t)=2t+5 we have g(3)=2*3+5=11

Now, f(3)-g(3)= -2 - 11 = -13

User Yue You
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.